2017
DOI: 10.1186/s13148-017-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

Methods and novel technology for microRNA quantification in colorectal cancer screening

Abstract: The screening and diagnosis of colorectal cancer (CRC) currently relies heavily on invasive endoscopic techniques as well as imaging and antigen detection tools. More accessible and reliable biomarkers are necessary for early detection in order to expedite treatment and improve patient outcomes. Recent studies have indicated that levels of specific microRNA (miRNA) are altered in CRC; however, measuring miRNA in biological samples has proven difficult, given the complicated and lengthy PCR-based procedures use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 149 publications
0
23
0
1
Order By: Relevance
“…In pancreatic cancer, different patterns have been found in miRNA expression profiles, which have contributed to the development of a miRNANome between the normal and cancerous pancreas [60]. Determination of these miRNA expression profiles has been made possible through different gene profiling methods, mainly microarrays, RNA-sequencing, and RT-PCR analysis of specimens [61]. Due to the stability of miRNA in circulation, blood screening could be employed as an approach to detect specific miRNA which have been linked with stage, survival rate or aggressiveness of the disease [62–64].…”
Section: Main Textmentioning
confidence: 99%
“…In pancreatic cancer, different patterns have been found in miRNA expression profiles, which have contributed to the development of a miRNANome between the normal and cancerous pancreas [60]. Determination of these miRNA expression profiles has been made possible through different gene profiling methods, mainly microarrays, RNA-sequencing, and RT-PCR analysis of specimens [61]. Due to the stability of miRNA in circulation, blood screening could be employed as an approach to detect specific miRNA which have been linked with stage, survival rate or aggressiveness of the disease [62–64].…”
Section: Main Textmentioning
confidence: 99%
“…An increasing number of studies have confirmed that miRNAs are active participants in the development of CRC (26,27). In addition, these small non-coding RNAs are regarded as key regulators of metastasis and EMT in human cancers (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional detection methods for miRNAs are qPCR, microarray and next-generation sequencing, but no one method is completely ideal for clinical application. In order to meet clinical requirements, various methods such as isothermal amplification techniques and near-infrared technology have been established and have been summarized elsewhere [132].…”
Section: Regulation and Detection Of Mirnasmentioning
confidence: 99%